Inflation and distribution during the post-COVID recovery - Mark Setterfield (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2022)
The early stages of recovery from the recession induced by the COVID-19 pandemic have been accompanied by a marked increase in inflation in the US and elsewhere. Much has been made of this outcomes, and the economic distress associated with it, in popular discussion of the economy. This paper provides a Kaleckian conflicting-claims analysis of inflation during the post-COVID recovery, that distinguishes between rising wages, pandemic-related supply shocks, and corporate price-setting behaviour as sources of inflationary pressure. A key conclusion that arises from the co-determination of inflation and distributional outcomes in the Kaleckian framework is that distributional developments that have further disadvantaged working households, rather than inflation per se, are the chief source of recent economic distress - and should be the chief cause for concern among policy makers.
Keywords: E02; E11; E12; E25; E31; E64; 330; Inflation; COVID-19; conflicting claims; wage share; income distribution